Scope of the administrator's discretion in the rejection of mining rights: considerations about the indeterminate concepts of article 42 of the Brazilian Mining Code - Dammski, Luiz Paulo (Universidad Nacional del Litoral, 2021)
The exploitation of mining resources in Brazil is an activity that depends on technical analysis by the National Mining Agency and, as a last act, on concession by the Minister of Mines and Energy. The final decision in this process, however, may be due to the rejection of the mining request, through analysis and discretionary decision by the Minister of Mines and Energy. In spite of the discretion of such a decision, the rejection must be based on one of the two hypotheses contained in the legal permissive, both permeated by open concepts. Based on the reflection presented in this article, the aim is to explore the limits of the discretion of the public administration in the rejection of mining concession requests, in order to enable a visualization with greater scope of the administrator's discretion in case of denial of the concession claim. of mining formulated by the administrator.